2012
DOI: 10.1089/end.2011.0491
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Aspirin Is Safe in Patients Undergoing Urologic Robot-Assisted Surgery

Abstract: The administration of aspirin to patients undergoing robot-assisted radical prostatectomy and nephrectomy appears to be safe. The risk of cardiovascular complications resulting from stopping aspirin may exceed the risk of perioperative bleeding and associated complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“… and Parikh et al. , comprising 236 and 95 patients, have examined the influence of low‐dose aspirin intake on median blood loss and transfusion rates in patients undergoing RARP. Both sets of authors observed no significant differences in peri‐operative median blood loss and transfusion rates between patients in the RARP cohort with and without ongoing aspirin intake; however, the first study included only six patients in the aspirin group.…”
Section: Discussionmentioning
confidence: 99%
“… and Parikh et al. , comprising 236 and 95 patients, have examined the influence of low‐dose aspirin intake on median blood loss and transfusion rates in patients undergoing RARP. Both sets of authors observed no significant differences in peri‐operative median blood loss and transfusion rates between patients in the RARP cohort with and without ongoing aspirin intake; however, the first study included only six patients in the aspirin group.…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients analyzed had a transfusion. [6] Our patients stopped their aspirin use 7 days prior to surgery and thus is a different group of patients that the those in the studies described above, we also did not find differences in EBL or rates of grade 3–5 complications between our aspirin, no therapy and ACT patient cohorts. While there was a statistical significant difference in LOS amongst the cohorts it was not clinically relevant.…”
Section: Discussionmentioning
confidence: 65%
“…Several studies have looked at the effects of continued aspirin during robotic prostatectomy with one study also analyzing a small cohort of nephrectomy patients. [5, 6] Parikh et al analyzed 26 patients undergoing robotic nephrectomy, 14 on aspirin compared to 12 not on asprin, and found no differences in blood loss, operative time and LOS. None of the patients analyzed had a transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the OAT group in this study consisted of only 6 patients, limiting its statistical power and the conclusion. Subsequently, Parikh et al 26 and Binhas et al 27 presented their first data with larger cohorts regarding the implementation of laparoscopic radical prostatectomy/RARP under continuous OAT. They reported no significant differences in the transfusion rates and postoperative hemorrhagic complications.…”
Section: Mortezavi Et Almentioning
confidence: 99%
“…However, both studies reported significant differences in the preoperative parameters due to the lack of randomization or matching. Furthermore, no data on the oncological and early surgical outcome 26 or on the oncological outcome only 27 were presented. To achieve comparable groups, we performed a matching of patients according to tumor stage, nerve-sparing, and lymphadenectomy.…”
Section: Mortezavi Et Almentioning
confidence: 99%